DAMPAK PENYELENGGARAAN EVENT PIALA EROPA 2012 (UEFA EURO) TERHADAP EKONOMI DAN POLITIK UKRAINA - Yohana Kristin Marpaung; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study deals with the impact of UEFA EURO 2012 toward politic and economy of UEFA EURO 2012. The perspective applied in this study is liberalism with theory of national interest and globalization. The design of the study is analytical descriptive qualitative. The data is taken by using library research method.Nowadays, football is made as a multi – impact commodity. It also happens in Ukraine. Globalization leads Ukraine as one of UEFA EURO host in 2012. Ukraine gets big development both directly and indirectly through that event. The income of the country increases through the investment comes as the preparation of UEFA EURO 2012 and the availability of job vacancy which develop the growth of economy in Ukraine.Moreover, the economy of Ukraine grows and that mega event also impact the situation of politic in Ukraine. UEFA EURO has stabilized the politics within.Keywords : Impact, UEFA EURO 2012, Ukraine, Economy, Politic.